Autophagy fine-tuning by angiotensin-(1-9) in cultured rat cardiomyocytes - Bustamante, Mario; Quiroga, Clara; Mancilla, Georthan; Gomez, Wileidy; Tapia, Anita; Figueroa, Reinaldo; Mondaca-Ruff, David; Oyarzún, Ingrid; Verdejo, Hugo E.; Lavandero, Sergio; Castro, Pablo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe renin-angiotensin system (RAS) plays a pivotal role in regulating blood volume, systemic vascular resistance, and electrolyte balance, serving as a key component of cardiovascular health. Recent findings highlight the role of angiotensin II (Ang II) in inducing autophagy through angiotensin II receptor type 1 (AT1R). Autophagy, a process of self-degradation and turnover of cellular components, is a homeostatic response that eliminates superfluous materials. Abnormal autophagy promotes cardiomyocyte loss and is critical in hypertrophy and heart failure progression. The RAS's non-canonical axis, which includes the angiotensin 1-9 peptide [Ang-(1-9)], has an anti-hypertrophic effect in cardiomyocytes via an unknown mechanism. In the present study, we aimed to elucidate the effect of Ang-(1-9) on cardiomyocyte autophagy.MethodsWe isolated and cultured neonatal ventricular cardiomyocytes and then co-treated them with Ang-(1-9) in the presence of chloroquine (CQ), Ang-II, and chemical inhibitors of different signaling pathways. After treatment, total RNA and protein extracts were obtained to analyze the abundance of different autophagy markers. Likewise, cells were fixed, and autophagy was analyzed through epifluorescence microscopy.ResultsOur findings show that CQ leads to a reduction in autophagy markers, such as microtubule-associated protein 1 light chain 3-II (LC3-II) and total LC3, suggesting Ang-(1-9)'s regulatory role in basal autophagy levels. Furthermore, Ang-(1-9) opposes Ang-II-induced autophagy and induces the phosphorylation of the S234 residue of Beclin-1 (BCN1) via an angiotensin II receptor type 2 (AT2R)/Akt-dependent pathway.ConclusionsThis reduction of Ang-II-induced autophagy by Ang-(1-9) unveils a novel aspect of its action, potentially contributing to its cardioprotective effects.